Contextualizing the Concept of Women’s Empowerment and its Approaches in Indian Context - Kumar, Anand; Yadava, R. S.; Butola, B. S. (National Geographical Journal of India, 2022)
The present discourse on women’s empowerment is now trying to mainstream the gender concerns and engaging them in the development process of the country. Besides, it seeks to see women as more recipients of welfare benefits. In this article investigators try to envisage into the understanding of women’s empowerment perspectives. The study also tries to focus those development approaches which can accelerate to the pace of women’s empowerment. To study the gradual changes which have taken place in improving the status of women since Independence (1947) along with understanding improvements of their status. Data from Census of India, NSSO and National Crime Records Bureau (NCRB) show the contemporary scenario regarding demographic, health-care, educational, economic participation, decision-making conditions with the major social obstacles in path of women’s empowerment in Indian context.